Effect of partial replacement of meat with chickpea flour, soybean flour and skimmed milk powder on physicochemical and sensory evaluation properties of camel meat burger - Abdalbasit Adam Mariod; Mohamed Abd Elagdir (Cogent Food & Agriculture, 2024)
Camel meat contains a high percentage of unsaturated fatty acids that are beneficial for cardiovascular health and controlling cholesterol levels. This aims to evaluate the effect of partially replacing camel meat with chickpea flour (CPF), soybean flour (SBF), and skimmed milk powder (SMP) on the physicochemical and sensory evaluation properties of camel meat burgers. Ten burger formulations were prepared by partially replacing the minced meat with CPF, SBF, and SMP at percentages of 10%, 20%, and 30%. Proximate composition, pH, color, water holding capacity, cooking loss, and sensory evaluation were conducted. Significant increases (p < 0.05) in protein contents were observed in all treated samples, as the initial protein value of the control (17.2 ± 2.5) was significantly increased to between 20.1 ± 2.6 and 26.5 ± 0.2. The moisture content of all treated samples decreased significantly (p < 0.05), while fat and ash levels remained unchanged without significant (p > 0.05) increases. However, the partial replacement of meat with the CPF, SBF, and SMP resulted in significant (p < 0.05) decreases in the cooking loss ranging from 18 to 30%, depending on the type and percentage of CPF, SBF, and SMP replaced. The replaced burgers obtained high overall acceptance scores ranging from 7.1 to 8.8 compared to the control. It is strongly recommended to partially replace the camel minced meat with CPF, SBF, and SMP to improve the physicochemical and sensory properties of the produced burger. Thus, the study proved that new burger formulations of CPF, SBF, and SMP significantly had high protein content and high consumption acceptability scores.